Assessing the effects of limestone dust and lead pollution on the ecophysiology of some selected urban tree species - Sabir, Muhammad Azeem; Guo, Wei; Nawaz, Muhammad Farrakh; Yasin, Ghulam; Yousaf, Muhammad Talha Bin; Gul, Sadaf; Hussain, Tanveer; Rahman, Shafeeq Ur (Frontiers in Plant Science, 2023)
Soil and air pollution caused by heavy metals and limestone dust from anthropogenic activities are prevalent and an alarming threat to the environment and humans. This study was conducted to evaluate the growth and physiological response of three tree species, Bombax ceiba, Eucalyptus camaldulensis, and Conocarpus lancifolius, under the individual as well as synergetic effects of heavy metal lead (Pb) and limestone dust toxicities. The tree species were grown under controlled environmental conditions with nine treatments having three levels of dust (0, 10, and 20 g) along with three levels of Pb (0, 5, and 10 mg L−1) with the following arrangement: T1 (control), T2 (10 g dust), T3 (20 g dust), T4 (5 mg L−1 Pb), T5 (10 g dust + 5 mgL−1 Pb), T6 (20 g dust + 5 mgL−1 Pb), T7 (10 mgL−1 Pb), T8 (10 g dust + 10 mg L−1 Pb), and T9 (20 g dust + 10 mgL−1 Pb) with three biological replicates. The results showed that B. ceiba, followed by E. camaldulensis, performed better under the same levels of Pb and limestone dust pollution. The B. ceiba tree species proved to be most tolerant to Pb and limestone pollution by efficiently demolishing oxidative bursts by triggering the following: CAT by 3.3%, 9.4%, 12.1%, 14.7%, 19.4%, 19.4%, 21.6%, and 23.6%; SOD by 4.1%, 7.1%, 9.5%, 11.1%, 12.2%, 14.8%, 16.8%, and 19.5%; POD by 4.3%, 6.4%, 8.3%, 10.2%, 12%, 15.4%, 18.5%, and 18.7%; and proline contents by 7.9%, 10.8%, 15.9%, 24.7%, 27.5%, 27.5%, 29.3%, and 32.5% in T2, T3, T4, T5, T6, T7, and T8, respectively, as compared to T1 (control). Based on our findings, we strongly suggest planting B. ceiba followed by E. camaldulensis tree species in heavy metal- and limestone dust-polluted areas due to their better performance and efficient heavy metal-scavenging capability.